2015
DOI: 10.1097/olq.0000000000000302
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence and Correlates With Risk Behaviors and HIV/STI Diagnoses Among Men Who Have Sex With Men and Men Who Have Sex With Men and Women in China

Abstract: Background Intimate partner violence (IPV) research has primarily focused on heterosexual couples, but has largely ignored IPV among men who have sex with men (MSM). We examined IPV prevalence among MSM and men who have sex with men and women (MSMW) in China. Methods MSM over the age of 16 were recruited through three MSM-focused websites in China. An online survey containing items on sociodemographics, risk behaviors, IPV, and self-reported HIV or STI diagnosis was completed. Multivariate regression was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
37
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 29 publications
(37 reference statements)
8
37
1
Order By: Relevance
“…Further mixed methods research could provide critical information about the patterning of these experiences with MSM living with HIV. The observed prevalence of any IPV (23.7%) in our study is in accordance with the rates among Chinese MSM in other studies (24-29%) [14,16], but is higher than general males (7.6%) [49]. The prevalence of physical IPV experience in our study participants is higher than that among MSM in a Shanghai study (16.6% vs. 6.6%), whereas the rates of psychological IPV (7.4% vs. 8.2%) and sexual IPV (5.2% vs. 5.5%) were nearly the same [16].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Further mixed methods research could provide critical information about the patterning of these experiences with MSM living with HIV. The observed prevalence of any IPV (23.7%) in our study is in accordance with the rates among Chinese MSM in other studies (24-29%) [14,16], but is higher than general males (7.6%) [49]. The prevalence of physical IPV experience in our study participants is higher than that among MSM in a Shanghai study (16.6% vs. 6.6%), whereas the rates of psychological IPV (7.4% vs. 8.2%) and sexual IPV (5.2% vs. 5.5%) were nearly the same [16].…”
Section: Discussionsupporting
confidence: 92%
“…Globally, prevalence rates among MSM range from 32 to 78% for experiencing any form of IPV [5,6], 12 to 45% for physical IPV [7,8], 5 to 33% for sexual IPV [8,9], and 28 to 64% for emotional/psychological IPV [10,11]. IPV has been associated with higher levels of potentially risky sexual behaviors, such as condomless sex [5,12,13], group sex [14], commercial and casual sex, as well as increased risks for substance abuse [15] and sexually transmitted infection [16].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in the final model, more experiences of sexual violence in the past 12 months were independently associated with not living with a spouse or steady partner, having a history of childhood sexual abuse, more adult experiences of homophobia, and higher scores on depression and hostility symptoms (see Table 2). Since previous research has shown differences between MSM and men who have sex with men and women (MSMW) in terms of sexual violence and other psychosocial factors (Davis et al, 2015; Dyer, Regan, Pacek, Acheampong, & Khan, 2015; Wang et al, 2015), we re-ran the hierarchical regression model excluding 48 participants who reported sex with women in the past two months. The substantive findings were mostly unchanged.…”
Section: Resultsmentioning
confidence: 99%
“…Also, studies in LMIC have identified key differences between MSM and MSMW. It has been shown that MSMW have greater risk of intimate partner violence (Davis et al, 2015), higher HIV prevalence, greater likelihood of trading sex, greater use of alcohol and illicit drugs (Wang et al, 2015), lower odds of prior HIV testing (Bowring, Veronese, Doyle, Stoove, & Hellard, 2016), and more inconsistent use of condoms with male partners (Ramakrishnan et al, 2015) compared to MSM only. Accordingly, future studies should examine correlates of sexual violence victimization in separate models for MSM and MSMW.…”
Section: Discussionmentioning
confidence: 99%
“…Although many HIV prevention intervention programs highlight Chinese MSM as a key population, MSM are documented to continue with a high prevalence of risky behaviors, such as condomless anal sex, substance abuse, multiple sexual partnership and lack of routine HIV testing [3][4][5][6][7]. Hence, continued HIV transmission occurs within and beyond this population through both homosexual and heterosexual contacts [8].…”
Section: Introductionmentioning
confidence: 99%